Comparative evaluation of corneal incision enlargement after intraocular lens delivery of new preloaded and manual implantation systems. Issue 1 (January 2021) - Wang, Lixin; Wolfe, Patricia; Paliwal, Sumit; Chernosky, Alexis; Kohnen, Thomas
Purpose: To determine whether total corneal incision enlargement after implantation of an intraocular lens with a new preloaded delivery system is comparable to a standard-of-care manual delivery system using an in vitro human cadaver eye model, despite having a smaller initial incision size. Methods: Human cadaver phakic whole eye globes were used for these studies (n = 16 per group). Each pair of eyes was randomly assigned to a new preloaded delivery system (UltraSert TM ) or a manual delivery system (MONARCH ® III D). The surgical procedure included creating a 2.2- and 2.4-mm corneal incision for the preloaded and manual delivery systems, respectively, measuring intraocular pressure and pre-implantation corneal incision size, delivering the intraocular lens into the anterior chamber, and measuring the post-implantation incision size. Results: The final corneal incision enlargement after intraocular lens delivery using the preloaded delivery system was 2.33 ± 0.04 mm, compared to 2.54 ± 0.05 mm after intraocular lens delivery with the manual delivery system. The mean corneal incision enlargement was comparable between the two systems, being 0.13 ± 0.04 mm using the preloaded delivery system and 0.14 ± 0.05 mm using the manual delivery system (p = 0.432). Conclusion: In a human cadaver eye model, the preloaded delivery system demonstrated an intraocular lens delivery performance on cornea incision enlargement was noninferior to the manual, standard-of-care intraocular lens delivery system despite a smaller initial incision size. Translational relevance: Smaller incision sizes for cataract surgery improve patient outcomes via faster visual and wound recovery and decreased risk of complications such as postoperative inflammation and surgically induced astigmatism.